A new reconstruction of continental Treptichnus based on exceptionally preserved material from the Jurassic of Massachusetts. (16th June 2016) - Getty, Patrick R.; McCarthy, Thomas D.; Hsieh, Shannon; Bush, Andrew M.
Abstract: Continental deposits of the Early Jurassic East Berlin Formation in Holyoke, Massachusetts, have yielded an exceptional occurrence of the ichnogenus Treptichnus . Here, burrows are preserved in full relief within thin mud laminae between layers of fine-grained, cross-bedded sandstone. We studied these burrows to evaluate whether earlier explanations of burrow morphology are applicable to all Treptichnus . Our research focused on three questions. (1) Do the Holyoke Treptichnus have significant vertical relief? (2) Does the lack of projections in some of the Holyoke Treptichnus result from stratinomic sectioning through the bottom of the burrow? (3) Do expanded, bulbous ends of burrow segments result from sediment compaction? While addressing these questions, the Holyoke fossils were compared to syntype and topotype material of Treptichnus from the Carboniferous of Indiana. The Holyoke Treptichnus did not exhibit significant vertical relief, and the presence and absence of projections is explained by the positioning of new segments at different points along older ones. The bulbous ends of burrow segments resulted from trace-maker behavior, not sediment compaction. Drawing on the analysis of the Holyoke material, a new reconstruction is proposed that presents continental Treptichnus as a shallow mole-tunnel-like burrow produced just below the sediment surface. This reconstruction is consistent with the morphology of Recent Treptichnus -like burrows produced by fly (dipteran) larvae, which are considered the most likely makers of the Holyoke Treptichnus .